Current variations in childhood cancer supportive care in the Netherlands. Issue 4 (20th November 2015) - Loeffen, Erik A. H.; Mulder, Renée L.; van de Wetering, Marianne D.; Font‐Gonzalez, Anna; Abbink, Floor C. H.; Ball, Lynne M.; Loeffen, Jan L. C. M.; Michiels, Erna M. C.; Segers, Heidi; Kremer, Leontien C. M.; Tissing, Wim J. E.
Abstract : BACKGROUND: Current treatment strategies in pediatric oncology are intensive and lead to high survival rates but also to treatment‐related complications. Therefore, supportive care plays an increasingly important role. This study was designed to evaluate variations in supportive care practice in children with cancer in the Netherlands and adherence to selected existing international guidelines through an in‐depth review of local guidelines and protocols at all 6 Dutch pediatric cancer centers. METHODS: Based on shared expert opinion, a questionnaire regarding current supportive care practice was compiled. For each center, the required information was extracted from local supportive care guidelines, and the list was sent to a pediatric oncologist of that center to verify its correspondence with local daily practice. Subsequently, it was determined whether clinical practice was concordant (same in ≥ 5 of 6 centers), partly concordant (highly overlapping in ≥ 5 of 6 centers), or discordant (same in < 5 of 6 centers). Local practices were compared with strong recommendations from high‐quality, evidence‐based guidelines. RESULTS: The questionnaire comprised 67 questions regarding supportive care practice. Concordance was observed for 11 of 67 practice items (16%), partial concordance was observed for 6 of 67 practice items (9%), and discordance was observed for 50 of 67 practice items (75%). Adherence to strong recommendations of 4 high‐quality, evidence‐based guidelines varied but was generally low. CONCLUSIONS: Large variations exist in pediatric oncology supportive care practice, and this could negatively influence care. Adherence to existing evidence‐based guidelines and the development and implementation of new clinical practice guidelines have the potential of standardizing supportive care practice and thereby improving outcomes for children with cancer. Cancer 2016;122:642–650. © 2015 American Cancer Society . Abstract : Practice for 75% of evaluated supportive care practice items is discordant in a nationwide study. The development of and adherence to clinical practice guidelines for supportive care in childhood cancer have the potential to decrease practice variation and thereby improve outcomes.